Application of Inverse Problem Method in Investigation of Thermal Conductivity for PCMs - Yuan Yanping; Du Yanxia; Cheng Baoyi (Zhileng xuebao)
Based on the model of phase change heat conduction,an inverse problem method combining phase interface motion experiment and numerical calculation was developed to study the improvement of thermal conductivity when metal is added in PCMs(Phase Change Materials).The results show that the greater the thermal conductivity of metal,the higher the effective thermal conductivity of PCMs.It is indicated that when the added ratio of metal is the same,the improvement is greater for PCMs with low conductivity than that for PCMs with high conductivity.The results agree well with those in literature.